Efektifitas Kompres Hangat dan Kompres Plester dalam Penurunan Suhu Tubuh pada Bayi dengan Demam - Fitriani S Dentika; A Arniyanti (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
Introduction: Fever is the most common case in children, and almost all children have experienced it; some only have a low-grade fever, while others have a very high fever. Method: Qualitative research using case study design aims to describe the case studies obtained and carried out systematically in intensively collecting case study data for infant patients with fever. Result: Based on the results of case studies found, differences in the effectiveness of warm compresses and plaster compresses. Conclusion: The point of plaster compresses is faster than warm compresses in a decrease in body temperature in babies with fever. It is recommended that the family or mother apply a plaster compress to her baby with a fever because it is more effective at reducing body temperature